Using The Discovery Learning Model to Improve Students' Activities and Learning Outcomes in Vocational High School - Triyono, Triyono (Vidya Karya, 2024)
The objectives of this study are to stimulate more activity and enhance student learning. In this study, the Discovery Learning methodology is applied. This study follows the method of Kemmis and McTaggart's classroom action research. Thirty students from SMK Negeri 1 Cangkringan's XII ATR 1 class served as the study's subjects. Test papers were used to gauge student learning outcomes, while observation sheets were used to estimate student activities. The percentage technique is used to look at the connection between activity and student learning outcomes. Learning success is measured using three variables: the growth of the learning activity, the grade point average, and the proportion of students who finish. The findings revealed a propensity for student activity to rise in cycles 1 and 2. The average class score grew from cycle one to cycle two by 71.5 points to 85 points. More students finished the cycle, from 60% in cycle 1 to 86.7% in cycle 2. Thus, the discovery learning paradigm can enhance class XII students' engagement and learning outcomes.